Tinjauan Hukum Islam Tentang Pengelolaan Sistem Bagi Hasil Pada Ternak Sapi Pedaging (Studi Kasus Di Desa Sudalarang Kecamatan Sukawening Garut) - Abdillah, Syaik; Nursyahbani, Hilda (STAI Al Musaddadiyah Garut, 2023)
Cattle breeding is an activity to breed and cultivate cows, this is commonly done by people in rural areas, as well as in urban areas. The problem that is often faced by parties who are in the cattle business is when sharing the proportion of profits in the profit sharing agreement from the sale of cattle. Formulation of problems in research How is the implementation of the management of the broiler cattle production sharing system in Sudalarang Village, Sukawening District? and How Islamic law reviews the management of the production sharing system for broiler cattle in Sudalarang Village. The purpose of this study is to determine the implementation of the management of the broiler cattle production sharing system in Sudalarang Village, Sukawening District. As well as to find out the review of Islamic law on the management of the production sharing system for broiler cattle in Sudalarang Village, Sukawening District. This research is included in the type of qualitative research with data collection techniques used, namely interviews, observation, and documentation. From this data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it was found that research on the management of the broiler cattle production sharing system, a case study in Sudalarang Village, Sukawening District, Garut Regency, the first is a musyarakah contract. Second, the implementation of profit sharing established between capital owners and capital maintainers has been justified by Shara because it is in accordance with the requirements and pillars of Musharakah profit sharing. However, in the latest findings there is an oddity that such a process may have one of the parties disadvantaged even though it has gone through the interadhin process. Keywords: Islamic Law, Profit Sharing, Livestock, Broiler Cattle